2017
DOI: 10.1007/s11684-017-0575-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in granulosa cells contributes to poor oocyte quality and IVF-ET outcomes in women with polycystic ovary syndrome

Abstract: The increased levels of intracellular reactive oxygen species (ROS) in granulosa cells (GCs) may affect the pregnancy results in women with polycystic ovary syndrome (PCOS). In this study, we compared the in vitro fertilization and embryo transfer (IVF-ET) results of 22 patients with PCOS and 25 patients with tubal factor infertility and detected the ROS levels in the GCs of these two groups. Results showed that the PCOS group had significantly larger follicles on the administration day for human chorionic gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 34 publications
7
93
0
1
Order By: Relevance
“…Apart from direct damage inflicted on oocytes by oxidative stress, granulosa cell function may be impaired, adding indirectly to functional impairment of associated oocytes. Evidence of oxidative stress in granulosa cells recovered along with oocytes for human in vitro fertilization was more severe for oocytes that failed to become fertilized or develop to blastocyst stage (Ávila et al, 2016;Lai et al, 2018), indicating that oxidative stress, at least at the antral stage of follicular development, has a detrimental effect on the follicle and oocyte.…”
Section: Oxidative Stress Contributes To Infertilitymentioning
confidence: 99%
“…Apart from direct damage inflicted on oocytes by oxidative stress, granulosa cell function may be impaired, adding indirectly to functional impairment of associated oocytes. Evidence of oxidative stress in granulosa cells recovered along with oocytes for human in vitro fertilization was more severe for oocytes that failed to become fertilized or develop to blastocyst stage (Ávila et al, 2016;Lai et al, 2018), indicating that oxidative stress, at least at the antral stage of follicular development, has a detrimental effect on the follicle and oocyte.…”
Section: Oxidative Stress Contributes To Infertilitymentioning
confidence: 99%
“…) and in the ovarian granulosa cells (Lai et al . ) of PCOS patients. In support of these clinical findings, previous studies by us and others have also reported that PCOS‐like rodents exhibit increased ovarian ROS levels and decreased ovarian and uterine superoxide dismutase (SOD) levels (Ullah et al .…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the expression of several other negative regulators of ferroptosis such as Ho1 (heme oxygenase 1) (6) and Mt1g (metallothionein 1G) (20) are downregulated in the gravid uterus after combined maternal exposure to DHT and INS (18). Increased circulating ROS levels have been observed in both non-pregnant and pregnant rodents in which PCOS features have been induced (19, 21). Elevated ROS production and decreased anti-oxidative capacity has been observed in the ovarian granulosa cells and leukocytes of PCOS patients (21-23), and oxidative stress is proposed to contribute to miscarriage and infertility in women with PCOS (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Increased circulating ROS levels have been observed in both non-pregnant and pregnant rodents in which PCOS features have been induced (19, 21). Elevated ROS production and decreased anti-oxidative capacity has been observed in the ovarian granulosa cells and leukocytes of PCOS patients (21-23), and oxidative stress is proposed to contribute to miscarriage and infertility in women with PCOS (24, 25). It is therefore likely that the promotion of pathologic oxidative stress and activation of ferroptosis in the gravid uterus and placenta contribute to HAIR-induced fetal loss in both animal models and humans.…”
Section: Introductionmentioning
confidence: 99%